PERANAN KOPERASI TANI UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA TINDALLUN KECAMATAN ANGGERAJA KABUPATEN ENREKANG - suparman suparman (Universitas Muhammadiyah Enrekang, 2019)
This study aims to determine the Role of Farmers Cooperatives to improve the welfare of the people of Tindallun Village, Anggerja District, Enrekang Regency.In this study, the authors used a descriptive qualitative method. This research is located in the Tani Village Cooperative Tindallun, Anggeraja District, Enrekang Regency. The population and sample in this study were administrators and employees of the Village Cooperative Farmers of Tindallun, totaling 110 people. To obtain the data needed in this study used interview, observation and questionnaire techniques. While the analysis techniques used are Data Collection, Data Reduction, Data Presentation and Conclusion Drawing.The results of the study are obtained results of research on (1) What efforts undertaken by the Farmers Cooperative to improve the welfare of the community Tindallun Village Anggeraja District Enrekang Regency is Running a business in the economic field, Running a business in marketing, Running a business in the field of services, namely electricity service units and Business in the social field. (2) The constraints faced by the Farmers Cooperative to improve the welfare of the community of Tindallun Village, Anggeraja District, Enrekang Regency are the lack of capital, the location of the office is less strategic, bad credit and the low participation of members. (3) Efforts made by the Tindallun Village Farmers Cooperative in improving the welfare of the community of Tindallun Village, regarding: capital fertilization, making brochures on the location and location, as well as the businesses carried out by the Tindallun Village Farmers Cooperative, Write-off long-term loans with interest low, as well as providing counseling about cooperatives, especially regarding the importance of the role of members in a cooperative. Because the member function is the owner and user of the cooperative service.